Impact of sequential (first- to third-generation) EGFR-TKI treatment on corrected QT interval in NSCLC patients - Gan, Tian; Chen, Jindong; Wang, Hao; Shang, Conghui; Xi, Siqi; Fan, Zixu; He, Ben; Zhang, Min; Zhao, Liang (Frontiers in Oncology, 2024)
Objective To evaluate the impact of sequential (first- to third-generation) epidermal growth factor receptor tyrosine kinase inhibitor (EGFR-TKI) treatment on top-corrected QT interval (top-QTc) in non-small cell lung cancer (NSCLC) patients. Methods We retrospectively reviewed the medical records of NSCLC patients undergoing sequential EGFR-TKI treatment at Shanghai Chest Hospital between October 2016 and August 2021. The heart rate (HR), top-QT interval, and top-QTc of their ECGs were extracted from the institutional database and analyzed. Logistic regression was performed to identify predictors for top-QTc prolongation. Results Overall, 228 patients were enrolled. Compared with baseline (median, 368 ms, same below), both first-generation (376 ms vs. 368 ms, p < 0.001) and sequential third-generation EGFR-TKIs (376 ms vs. 368 ms, p = 0.002) prolonged top-QT interval to a similar extent (p = 0.635). Top-QTc (438 ms vs. 423 ms, p < 0.001) and HR (81 bpm vs.79 bpm, p = 0.008) increased after first-generation EGFR-TKI treatment. Further top-QTc prolongation (453 ms vs. 438 ms, p < 0.001) and HR increase (88 bpm vs. 81 bpm, p < 0.001) occurred after treatment advanced. Notably, as HR elevated during treatment, top-QT interval paradoxically increased rather than decreased, and the top-QTc increased rather than slightly fluctuated. Moreover, such phenomena were more significant after treatment advanced. After adjusting for confounding factors, pericardial effusion and lower serum potassium levels were independent predictors of additional QTc prolongation during sequential third-generation EGFR-TKI treatment. Conclusion First-generation EGFR-TKI could prolong top-QTc, and sequential third-generation EGFR-TKI induced further prolongation. Top-QT interval paradoxically increased and top-QTc significantly increased as HR elevated, which was more significant after sequential EGFR-TKI treatment. Pericardial effusion and lower serum potassium levels were independent predictors of additional QTc prolongation after sequential EGFR-TKI treatment.